Relationship between age and size of firm on corporate entrepreneurial behaviour among employees / Zarinah Abu Yazid and Al-Mansor Abu Said - Abu Yazid, Zarinah; Abu Said, Al-Mansor (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Previous innovation literature regarding firm age, firm size and innovation has received a great deal of attention. Some arguments proposed that large firms were more effective innovators than smaller firms. However, there are arguments that smaller firms are more flexible, better able to adapt and effect change, and experience more advantages in innovation. This study therefore, attempts to examine whether size and age of firm has influence the level of corporate entrepreneurial behaviour among employees. Across-sectional survey was used to determine how the independent variables influence the corporate entrepreneurial behaviour within manufacturing sectors in Malaysia. The population consisted of 155 respondents from six multinational corporations (MNC) in Klang Valley and Penang. The six companies were manufacturing-based companies. Findings revealed that size, as a company’s characteristic did not influence corporate entrepreneurial behaviour. However, the age of companies showed a negative relationship with corporate entrepreneurial behaviour and the internal antecedents.